Stability and Hopf Bifurcation of Stationary Solution of a Delay Equation (Journal of Partial Differential Equations, 2000)
In this paper we investigate a Logistic equation with delay and it is shown that if b(x) > c(x), the stationary solution is globally asymptotically stable; if τ is small, U(x) is locally stable; if b(x) < c(x). there is Hopf bifurcation from U(x).
Keywords: Logistic equation; delay; stability: Hopf bifurcation